Assessment of the knowledge and use of hypertonic saline among doctors working in paediatrics departments of tertiary institutions in the five states of South-East Nigeria - Ndu, Ikenna; Edelu, Benedict; Iloh, Kenechukwu; Nduagubam, Obinna; Ihejı, Chukwunonso Chıgozıe; Ezeudu, Chijioke; Ezeogu, Joseph; Igbokwe, Obianuju Ojinika; Iloh, Ogochukwu Nneka; Izuka, Oluchi Mildred; Nwokeji-onwe, Linda; Onu, Ngozi (The European Research Journal, 2023)
Objectives: This study aimed to evaluate the knowledge and use of hypertonic saline among doctors in the Southeast region of Nigeria. Methods: It was a cross-sectional study conducted amongst 182 doctors in the paediatric departments of the six tertiary institutions in South Eastern Nigeria. Data to assess knowledge and use of hypertonic saline were collected using self-administered, structured questionnaires. Results: After aggregating the knowledge questions (definition of hypertonic saline, knowledge of available concentrations and modes of administration) and categorizing knowledge into good or poor, 148 (81.3%) had good knowledge, while 34 (18.7%) had poor knowledge. Respondents who had ever seen an infusion of hypertonic saline were 93 (51.1%), while only 62 (34.1%) had ever used it during their practice. Among those who had used it, only 33 (18.1%) obtained it from their hospital pharmacy. Most respondents (91.2%) would support advocacy for its increased availability and use in Nigeria. Conclusions: Our study demonstrated good knowledge of hypertonic saline, however, there is low usage due to unavailability. There is a need for collaboration between paediatricians, pharmaceutical companies and other stakeholders to create demand and initiate the production of hypertonic saline.